Electronic origin of hydrogen storage in MOF-covered palladium nanocubes investigated by synchrotron X-rays. Issue 1 (December 2018) - Chen, Yanna; Sakata, Osami; Nanba, Yusuke; Kumara, Loku; Yang, Anli; Song, Chulho; Koyama, Michihisa; Li, Guangqin; Kobayashi, Hirokazu; Kitagawa, Hiroshi
Abstract Hybrid materials composed of metal nanoparticles and metal-organic frameworks have attracted attention for various applications because of the synergistic functionality between their constituent materials. Interfacial interaction is expected however the mechanism remains ambiguous. Here we report the valence bands of palladium nanocubes covered by copper(II) 1, 3, 5-benzenetricarboxylate (HKUST-1), denoted as Pd@HKUST-1,  and the charge transfer from the palladium nanocubes to HKUST-1 at the Pd/HKUST-1 interface is investigated quantitatively. Interfacial density of states are different from those of internal constituents and imply that the Cu–O group in HKUST-1 acts as a charge accepter. The role of Cu–O group in charge transfer behaviour is also observed experimentally. Finally, we reveal the charge transfer mechanism from the Pd 4d bands to the Cu 3d (4sp ) – O 2p hybridization bands of HKUST-1 at the Pd/HKUST-1 interface, which explains the enhanced hydrogen storage capacity in Pd@HKUST-1. Transition metal nanoparticle-MOF systems have promising hydrogen storage properties but the nature of the interfacial interaction remains ambiguous. Here, the authors use computational and spectroscopic methods to investigate the electronic structure and charge transfer processes in a palladium nanocube-MOF system.